Folding of the syncytiotrophoblast basal plasma membrane increases the surface area available for exchange in human placenta. (January 2022) - Tashev, Stanimir A.; Parsons, Daisy; Hillman, Cameron; Harris, Shelley; Lofthouse, Emma M.; Goggin, Patricia; Chatelet, David S.; Cleal, Jane K.; Smyth, Neil; Palaiologou, Helen; Page, Anton; Lewis, Rohan M.
Abstract: Introduction: The placental syncytiotrophoblast is the primary barrier between the mother and the fetus. To cross the placenta, nutrients and wastes must be transported across the apical microvillous and basal plasma membranes. While the syncytiotrophoblast basal plasma membrane is typically represented as relatively smooth, it has been shown to have invaginations that may increase its surface area. This study aimed to quantify how folding of the syncytiotrophoblast basal membrane contributes to its surface area and to visualise three-dimensional structures of the basal membrane and cytotrophoblast cell structures. Methods: Transmission electron microscope images of human term placenta were analysed using stereological approaches to quantify how folding of the syncytiotrophoblast basal plasma membrane affected surface area. Serial block-face scanning electron microscopy was used to visualise the three-dimensional structure of the syncytiotrophoblast basal membrane and cytotrophoblast cells. Results: Syncytiotrophoblast basal membrane covered 69.1% of the basal lamina, with cytotrophoblast cells covering the remaining 30.9%. In basal lamina adjacent to syncytiotrophoblast, 34% was adjacent to smooth basal membrane and 66% to folded basal membrane. Syncytiotrophoblast basal membrane folds increased the surface area adjacent to basal lamina by 305%. Including regions overlying the cytotrophoblast cells, basal membrane folds increased syncytiotrophoblast basal membrane surface area by 4.4-fold relative to the basal lamina in terminal villi. Terminal and intermediate villi were similar in terms of trophoblast coverage of the basal lamina and basal membrane folding. The three-dimensional structures of the syncytiotrophoblast basal plasma membrane and cytotrophoblast cells were generated from serial block-face scanning electron microscopy image stacks. Discussion: These findings indicate that the surface area of the syncytiotrophoblast basal plasma membrane is far larger than had been appreciated. We suggest that these folds increase the surface area available for transport to and from the fetus. Changes in the extent of basal membrane folding could affect nutrient transfer capacity and underlie pathological fetal growth, including fetal growth restriction and macrosomia. Highlights: This study provides the first quantitative assessment of basal membrane folds. Basal membrane folds increase its surface four-fold relative to the basal lamina. Cytotrophoblast coverage of the basal lamina was 30%. 3D reconstruction of cytotrophoblast provides insight into their structure.